2010
DOI: 10.1002/sce.20430
|View full text |Cite
|
Sign up to set email alerts
|

Identifying elements critical for functional and sustainable professional learning communities

Abstract: ABSTRACT:In this paper, we examined data collected as part of a 5-year project designed to foster reform-based urban science teaching through teachers' communities of inquiry. Drawing upon a distributed leadership framework, we analyzed teacher "talk" during professional learning community (PLC) meetings. This analysis yielded five elements: teacher learning and collaboration, community formation, confidence in knowledge of content and guided inquiry, concerns about the impact of accountability measures on tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 32 publications
0
31
0
1
Order By: Relevance
“…Some argue that effective TLCs benefit from a specific content focus and location (e.g., Slavt, Nelson, & Kennedy, 2010) and be led by experts (e.g., Stein, Smith, & Silver, 1999). Others suggest that interschool TLCs can be effective (e.g., Richmond & Manokore, 2011) and that leadership should be distributed among the TLCs members (Stoll et al, 2006). Further research has found that the role of a coach was a critical factor in supporting a TLC (Grossman et al, 2001;Richmond & Manokore, 2011;Stein et al, 1999).…”
Section: Effective Professional Development and Teacher Learning Commmentioning
confidence: 94%
“…Some argue that effective TLCs benefit from a specific content focus and location (e.g., Slavt, Nelson, & Kennedy, 2010) and be led by experts (e.g., Stein, Smith, & Silver, 1999). Others suggest that interschool TLCs can be effective (e.g., Richmond & Manokore, 2011) and that leadership should be distributed among the TLCs members (Stoll et al, 2006). Further research has found that the role of a coach was a critical factor in supporting a TLC (Grossman et al, 2001;Richmond & Manokore, 2011;Stein et al, 1999).…”
Section: Effective Professional Development and Teacher Learning Commmentioning
confidence: 94%
“…And whether I like it or not [
] I really need to start marking papers. (Tasha, email) Informed by the relevant research literature (Louden 1992, Pedretti 1996, Brody and Hadar 2011, Richmond and Manokore 2011, these comments might be read as the teacher educators wanting to preserve the status quo and resisting our invitations to look 'beyond the nuts and bolts of teaching practice' (Pedretti 1996, p. 313) into their normative beliefs. However, this behavior in fact exemplified the tension between reflectively inquiring into experience and the pressure of daily practice.…”
Section: Amendments To the First Propositionmentioning
confidence: 99%
“…It depends on distributing authority at all levels of the organizations rather than it is centralized at the top (Kawar, 2012). The distributed style is able to enhance & facilitate learning by extension & functional learning communities, and create high levels of commitment as a result of certain practices of such as trust, cooperation, participation in decision making and problem solving (Richmond & Manokore, 2010). With more authority granted to teachers, empowerment and coaching both inside and outside classrooms (Firestone & Martinez, 2007).…”
mentioning
confidence: 99%